Being Overweight Is Associated With Greater Survival in ICU Patients: Results From the Intensive Care Over Nations Audit*. Issue 12 (December 2015) - Sakr, Yasser; Alhussami, Ilmi; Nanchal, Rahul; Wunderink, Richard G.; Pellis, Tommaso; Wittebole, Xavier; Martin-Loeches, Ignacio; François, Bruno; Leone, Marc; Vincent, Jean-Louis
Abstract : Objective: To assess the effect of body mass index on ICU outcome and on the development of ICU-acquired infection. Design: A substudy of the Intensive Care Over Nations audit. Setting: Seven hundred thirty ICUs in 84 countries. Patients: All adult ICU patients admitted between May 8 and 18, 2012, except those admitted for less than 24 hours for routine postoperative monitoring (n = 10, 069). In this subanalysis, only patients with complete data on height and weight (measured or estimated) on ICU admission in order to calculate the body mass index were included (n = 8, 829). Interventions: None. Measurements and Main Results: Underweight was defined as body mass index less than 18.5 kg/m 2, normal weight as body mass index 18.5–24.9 kg/m 2, overweight as body mass index 25–29.9 kg/m 2, obese as body mass index 30–39.9 kg/m 2, and morbidly obese as body mass index greater than or equal to 40 kg/m 2 . The mean body mass index was 26.4 ± 6.5 kg/m 2 . The ICU length of stay was similar among categories, but overweight and obese patients had longer hospital lengths of stay than patients with normal body mass index (10 [interquartile range, 5–21] and 11 [5–21] vs 9 [4–19] d; p < 0.01 pairwise). ICU mortality was lower in morbidly obese than in normal body mass index patients (11.2% vs 16.6%; p = 0.015). In-hospital mortality was lower in morbidly obese and overweight patients and higher in underweight patients than in those with normal body mass index. In a multilevel Cox proportional hazard analysis, underweight was independently associated with a higher hazard of 60-day in-hospital death (hazard ratio, 1.32; 95% CI, 1.05–1.65; p = 0.018), whereas overweight was associated with a lower hazard (hazard ratio, 0.79; 95% CI, 0.71–0.89; p < 0.001). No body mass index category was associated with an increased hazard of ICU-acquired infection. Conclusions: In this large cohort of critically ill patients, underweight was independently associated with a higher hazard of 60-day in-hospital death and overweight with a lower hazard. None of the body mass index categories as independently associated with an increased hazard of infection during the ICU stay. Abstract : Supplemental Digital Content is available in the text.